Clinoptilolite foams prepared by alkali activation of natural zeolite and their post-synthesis modifications - Tišler, Zdeněk; Horacek, Jan; Safar, Jan; Velvarska, Romana; Peliskova, Lenka; Kocík, Jaroslav; Gherib, Yosra; Marklova, Kristyna; Bulánek, Roman; Kubicka, David (Elsevier Science BV, 2019)
Alkaline activated aluminosilicate materials have been studied mainly in the building industry as a substitute for concretes, ceramic materials and thermal insulations, but their properties predispose them to much greater use in the chemical industry. The aim of this study is to determine whether the alkaline activated natural zeolites can be modified to obtain a suitable chemical and textural properties for catalyst supports or sorbents. The alkaline activated natural zeolites with the clinoptilolite structure were foamed using Al powder and H2O2 solution. The prepared foam pellets were post-synthetically modified by HCl leaching and analyzed to compare their properties by XRF, XRD, N-2 physisorption, Hg porosimetry, DRIFT, TGA, SEM and the cutting-edge strength methods. The analysis showed that the clinoptilolite structure of the basic raw zeolite was partially preserved and porous materials had sufficient strength, a density of about 0.8 g/cm(3) and a specific surface area up to 160 m(2)/g making them suitable as catalyst supports or sorbents.
Klinoptilolitové pěny připravené pomocí alkalické aktivace přírodních zeolitů a jejich následné modifikace
Keywords: Natural zeolite; Clinoptilolite; Alkali activation; Inorganic foam; přírodní zeolit; klinoptilolit; alkalická aktivace; anorganické pěny